THE DEVELOPMENT OF AI IN THE HEALTH FIELD: A REVOLUTION FOR TORT LAW? - CAYOL, Amandine (MEDECINE LEGALE DROIT MEDICAL, 2025)
The development of the uses of artificial intelligence (AI) in the field of health raises questions about the adaptation of the legal rules applicable in case of damage resulting from it. The paradigm shift would be such, according to some, with the development of an increasingly “strong” AI, that a true “revolution” in tort law would be necessary: the creation of a sui generis liability regime for AI would be necessary, and even the recognition of the liability of AI itself, which would then be recognized as a legal entity. In reality, there is no justification for such a revolution: both the ordinary law of liability and the special regime of liability for defective products are likely to evolve by simple adjustments in order to respond to the issues raised by the increasing use of AI.